2021
DOI: 10.3389/fonc.2021.671811
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Value of Preoperative Systemic Inflammatory Response Index (SIRI) in Patients With High-Grade Glioma and the Establishment of a Nomogram

Abstract: BackgroundThe predictive value of systemic inflammatory response index (SIRI) was confirmed in some malignant tumors. However, few studies investigated the prognostic value of SIRI in high-grade gliomas. This study aimed to evaluate the prognostic relationship of preoperative SIRI in high-grade gliomas and established a nomogram accordingly.MethodsData of operable high-grade glioma patients were analyzed. Kaplan-Meier, log-rank test, cox regression and propensity score matching (PSM) analysis were used to anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 52 publications
0
27
0
3
Order By: Relevance
“… 8 As inflammatory indicators, the neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), lymphocyte to monocyte ratio (LMR) and red blood cell distribution width (RDW) have been reported to be predictive of stroke prognosis, but their formulations are relatively homogeneous and not comprehensive. 9 , 10 It has been reported that the novel chronic low-grade inflammatory index systemic immunity-inflammation index (SIRI) has excellent predictive power in glioma, 11 breast cancer 12 and nasopharyngeal carcinoma; 13 however, no studies have attempted to investigate its role in prediction in stroke prognosis.…”
Section: Introductionmentioning
confidence: 99%
“… 8 As inflammatory indicators, the neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), lymphocyte to monocyte ratio (LMR) and red blood cell distribution width (RDW) have been reported to be predictive of stroke prognosis, but their formulations are relatively homogeneous and not comprehensive. 9 , 10 It has been reported that the novel chronic low-grade inflammatory index systemic immunity-inflammation index (SIRI) has excellent predictive power in glioma, 11 breast cancer 12 and nasopharyngeal carcinoma; 13 however, no studies have attempted to investigate its role in prediction in stroke prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Some previous studies [ 34 38 ] have investigated the role of NLR, PLR, MLR, and AGR in GBM, but there was no consistent conclusion. In our study, we did not find the prognostic values of NLR, PLR, MLR, and AGR for the survival of GBM.…”
Section: Discussionmentioning
confidence: 92%
“…Although the SIRI (M × N/L) formula is similar to the SII (P × N/L) formula, where simply the monocytes in the SIRI substitute the platelets of the SII, a relationship between SIRI and GBM survival results was not found. According to Erkan Topkan’s conclusions, SIRI played a crucial role in survival prediction in glioblastoma multiforme patients treated with standard protocol [ 34 ]. We speculated that the causes presumably were that SIRI served as a dynamic indicator, and its value fluctuates during treatment, affecting final results.…”
Section: Discussionmentioning
confidence: 99%
“…32 Many studies have used similar approaches. 11,[33][34][35][36] Previous studies have evaluated the diagnostic potential of single or combined hematological indicators in gliomas. 11 They thought that NLR, as a single predictive marker, was the best predictor of glioma; however, age + PNI and age + AGR were the best combination indicators to forecast the diagnosis of glioblastoma or IDH-wt glioblastoma.…”
Section: Discussionmentioning
confidence: 99%